2019
DOI: 10.1037/amp0000321
|View full text |Cite
|
Sign up to set email alerts
|

The source model of group threat: Responding to internal and external threats.

Abstract: We introduce a model of group threat that articulates the opposing effects of intergroup (between-groups) and intragroup (within-group) threat on identity processes and group relations. The source model of group threat argues that the perceived source of a threat is critical in predicting its consequences, such that perceptions of intergroup threat will strengthen (in)group identity processes and relations, whereas perceptions of intragroup threat has the potential to undermine the same. In addition to reviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 98 publications
4
59
0
Order By: Relevance
“…Our results demonstrated that the Chinese public exhibited a supportive attitude toward the epidemic prevention measures during the most serious period of the COVID-19 epidemic, and the more information individuals browsed through regarding the epidemic, the greater their supportive attitude was, thus supporting Hypothesis 2. Chinese public exhibited a high degree of cooperation, which is consistent with previous findings that public tend to take effective and adaptive collective actions during disasters when provided with useful information and coping strategies (Glik, 2007;Greenaway & Cruwys, 2019). More importantly, the amount of epidemic…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results demonstrated that the Chinese public exhibited a supportive attitude toward the epidemic prevention measures during the most serious period of the COVID-19 epidemic, and the more information individuals browsed through regarding the epidemic, the greater their supportive attitude was, thus supporting Hypothesis 2. Chinese public exhibited a high degree of cooperation, which is consistent with previous findings that public tend to take effective and adaptive collective actions during disasters when provided with useful information and coping strategies (Glik, 2007;Greenaway & Cruwys, 2019). More importantly, the amount of epidemic…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, public's attitude may depend on epidemic information they acquire (Yamashita, 2012). During or after disasters such as an epidemic, when useful information about epidemic as well as its coping strategies are provided, individuals tend to exhibit more affinity or voluntary behavior, leading to public's effective and adaptive collective actions (Glik, 2007;Greenaway & Cruwys, 2019). Furthermore, epidemic information may promote public risk communication through timeously updating the updated information about epidemic.…”
Section: Epidemic Information and Attitude Toward Epidemic Prevention Measuresmentioning
confidence: 99%
“…This may be because destroying a symbol constitutes a distinctiveness threat per se, no matter who the perpetrators are (Firth, 1973; Welch, 2000), and ingroup bias is one of the most prevalent defensive reactions to threats to ingroup distinctiveness (e.g., Jetten, Spears, & Postmes, 2004). The ways in which ingroup versus outgroup threats to the ingroup impact intergroup relations and processes have rarely been examined (Greenaway & Cruwys, 2018). Therefore, how and when flag-burning perceived as criticism and flag-burning perceived as aggression, or situations involving ingroup versus outgroup flag burners, lead to similar or different intergroup effects would be an interesting subject for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in response to the threat to the ingroup's image caused by ingroup flag burning, blind patriots could defend their national identity through an increase in ingroup bias. In other words, when facing an ingroup symbol being desecrated by a member of the ingroup (i.e., an internal threat coming from the deviance of a group member), the reaction of other ingroup members could have repercussions on intergroup attitudes and the evaluation of outgroups (see Greenaway & Cruwys, 2018, for similar arguments).…”
Section: Ingroup Symbol Desecration: a Threat To Social Identity Among Blind Patriotsmentioning
confidence: 99%
“…Although members threatening their ingroup are part of the life of social and national groups, investigations of the intergroup consequences of these threats are relatively rare (Greenaway & Cruwys, 2018). The literature suggests that attacks on both ingroup and outgroup national symbols by an ingroup member could be perceived as deviant and therefore lead to a perception of a threat to national identity.…”
Section: Overview and Hypothesesmentioning
confidence: 99%